2002
DOI: 10.1364/oe.10.001573
|View full text |Cite
|
Sign up to set email alerts
|

Derivative analysis of absorption features in hyperspectral remote sensing data of carbonate sediments

Abstract: This study uses derivative spectroscopy to assess qualitative and quantitative information regarding seafloor types that can be extracted from hyperspectral remote sensing reflectance signals. Carbonate sediments with variable concentrations of microbial pigments were used as a model system. Reflectance signals measured directly over sediment bottoms were compared with remotely sensed data from the same sites collected using an airborne sensor. Absorption features associated with accessory pigments in the sedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 4 publications
0
44
1
2
Order By: Relevance
“…The derivative spectra (δ) were calculated using a finite approximation method (Louchard et al 2002), after smoothing the reflectance spectra with a natural cubic spline function (60 nodes). The second derivative (δδ) was chosen because in theory it eliminates the background effects and strongly enhances minute changes in the reflectance spectra.…”
Section: Methodsmentioning
confidence: 99%
“…The derivative spectra (δ) were calculated using a finite approximation method (Louchard et al 2002), after smoothing the reflectance spectra with a natural cubic spline function (60 nodes). The second derivative (δδ) was chosen because in theory it eliminates the background effects and strongly enhances minute changes in the reflectance spectra.…”
Section: Methodsmentioning
confidence: 99%
“…Hochberg and Atkinson 2 used Advanced Airborne Hyperspectral Imaging System imagery, and Andréfouët et al 3 used the Compact Airborne Spectrometer Imager for mapping and classification of benthic types into corals, algae, and sediments by fourth-derivative analysis of remotely sensed reflectance spectra. Louchard et al 4 used derivative analysis to classify carbonate sediments. Dierssen et al 5 used spectral ratios derived from Ocean PHILLS imagery of shallow Bahamian waters to extract bathymetry and bottom type; Louchard et al 6 used spectrum matching for the same purpose on the same imagery.…”
Section: Introductionmentioning
confidence: 99%
“…Kohler 18 compared PHILLS spectra from the 1999 version of this instrument with Hyper-TSRB data and found that both an offset and a gain were necessary to bring the PHILLS spectra into agreement with the Hyper-TSRB spectra. Louchard et al 4,6 also adjusted spectra from the 1999 version of the PHILLS instrument by subtracting the difference of a deep-water PHILLS spectrum and a HydroLight-computed spectrum for infinitely deep water from each shallow-water spectrum. We thus hypothesize that our PHILLS spectra are systematically too large, which is consistent with an undercorrection of atmospheric effects caused by using a 2 m s Ϫ1 wind speed in TAFKAA.…”
mentioning
confidence: 99%
“…Derivative spectroscopy has been used in a range of hyperspectral ocean studies to discriminate between healthy and unhealthy corals [255], to identify bottom types in shallow waters [256] and to classify different groups of phytoplankton [252,257,258]. A number of recent works have demonstrated the potential for this technique to analyse complex coastal waters [259,260] and atmospheric effects such as thin cirrus clouds and aerosols [253].…”
Section: Derivative Spectroscopymentioning
confidence: 99%